DI-071 Survey of good prescribing practices of new oral anticoagulants dabigatran and rivaroxaban. (24th February 2014) - Pelegrin, S; Audurier, Y; Ponrouch, M; Rosant, D; Roch-torreilles, I; Rambourg, P
Abstract : Background: The new oral anticoagulants present many advantages in terms of ease of use. However, no biological monitoring being indicated, it is important to respect the recommended dose and schedule to avoid the risks of over or under-dosing which might harm the patient. Purpose: To perform an inventory of prescribing practice of dabigatran and rivaroxaban in our hospital. Materials and methods: A retrospective study over 6 months (January–June 2013) was performed analysing the prescriptions for patients treated by dabigatran and rivaroxaban. The theoretical recommended doses (PTR) were determined based on 2 treatment charts issued by the Hospital Drug Committee then compared with doses actually prescribed. The parameters measured to determine the PTR were: indication, age, renal clearance (RCl) and associated drugs. Results: The marketing authorisation (MA) indications were followed for all prescriptions for both drugs. 20 patients were treated by dabigatran. 12 patients received a modified dose, 7 a non-adapted dose, and for 1 patient the PTR could not be determined in the absence of RCl. The seven non-adapted doses concerned: 2 overdoses (1 not adapted to the RCl and 1 interaction with acetylsalicylic acid), 3 under-dosing and 1 one contraindication (RCl less than 30 ml per min.). 26 patients were treated by rivaroxaban. 19 patients received a modified dose, 5 a non-adapted, and for 2 patients the PTR could not be determined because the indication was not found. The five non-adapted doses concern: 2 overdoses (non adaptation to the RCl), and 3 under-dosing. The recommendations for use of these drugs were respected in 67% of cases. 9% of patients presented an overdose, 15% under-dosing and 2% a contraindication. The overdoses concerned 3 absences of adaptation to the RCl and 1 interaction with another anticoagulant treatment. The under-dosing could be explained by other factors that could not be identified during the study (risk of haemorrhage, gastritis, GERD). Conclusions: Fewer than 70% of prescriptions complied with the recommendations drawn up by the Drug Committee of our hospital. Therefore, it is important that the pharmaceutical team should make prescribers aware of the need to adapt the dose of these 2 new anticoagulants to prevent drug-related harm. No conflict of interest.